A preliminary analysis of parent-child interaction therapy plus natural helper support to increase treatment access and engagement for low-income families of color. (March 2022) - Davis, Eileen M.; Garcia, Dainelys; Andrew Rothenberg, W.; Barnett, Miya L.; Davidson, Bridget; Espinosa, Natalie; Tonarely, Niza A.; Robertson, Emily L.; Alonso, Betty; San Juan, Juliet; Jent, Jason F.
Highlights: Natural helpers address disparities in access to behavioral parenting interventions. Natural helpers support recruitment and engagement of low-income families of color. Comparable clinical outcomes were achieved with natural helper support. Abstract: Disparities in care for low-income children of color call for innovative culturally and linguistically responsive solutions to better engage marginalized populations in evidence-based interventions. In partnership with a community organization, the addition of natural helper support as an adjunct to Parent-Child Interaction Therapy (PCIT + NH) was examined as a strategy to increase recruitment, engagement, and retention in PCIT for families historically unreached by a university-based clinic. Natural helpers provided home-based skills practice and support for forty-two families whose parents were more racially and linguistically diverse and had lower income and lower caregiver education than the typical population served by the same program (i.e., program population). Families who received PCIT + NH had comparable or higher rates of engagement relative to the program population and demonstrated improvements in clinical outcomes (i.e., decreased child externalizing and internalizing behaviors, increased child compliance, decreased caregiver stress, increased caregiver parenting skills) over the course of treatment. Furthermore, higher doses of natural helper support were associated with higher rates on most measures of treatment engagement (i.e., treatment completion, completion of the Child Directed Interaction phase of treatment, PCIT sessions, homework in the Parent Directed Interaction phase of treatment), with the exception of homework in the Child Directed Interaction phase of treatment and overall session attendance rate. Next steps for testing the treatment engagement and clinical outcome effects of the PCIT + NH model are discussed.